VATIS update : ozone layer protection. Vol. 4, No. 98, Jan-Feb 2010 - UN.ESCAP; Asian and Pacific Centre for Transfer of Technology (APCTT) (UN.ESCAP. Asian and Pacific Centre for Transfer of Technology, 2010)
VATIS Update Ozone Layer Protection is published 6 times a year to keep the readers up to date of most of the relevant and latest technological developments and events in the field of Ozone Layer Protection. The Update is tailored to policy-makers, industries and technology transfer intermediaries. Highlights : Ozone hole repair contributes to global warming -- New absorption technology -- Environment-friendly grease trap cleaner -- Hybrid fire suppression system -- Production of 'green' polyols -- Solar power to kill weeds THE SCIENCE OF OZONE LAYER . 4 -- Significant ozone hole remains over Antarctica -- Ozone hole repair contributes to global warming, says study -- Antarctic’s optical properties -- CFCs proved to cause ozone depletion ODS PHASE-OUT IN INDIA . 6 -- Experts advocate adoption of CFC-free inhalers IN THE NEWS . 6 -- India, Nepal to discuss green custom drive -- New CFC-free initiative -- New refrigerant gets European patent -- Maldives to phase out HCFCs -- Coca-Cola goes for HFC-free vending machines -- SAE International’s nod to new MAC refrigerant -- New CFC-free inhaler in Bangladesh market REFRIGERATION/AIR-CONDITIONING . 9 -- HCFC-free refrigerants -- Frictionless centrifugal chiller -- Performance of alternative refrigerant R430A -- New absorption technology for efficient heating and cooling -- Cascading CO2 refrigeration system -- Geothermal heat pumps SOLVENTS . 11 -- Environment-friendly grease trap cleaner -- Degreasing/drying solvent -- Bi-solvent-based cleaning of precision components -- Plastic-safe universal cleaner HALONS . 12 -- Halon replacement anti-fire products -- Clean agent fire suppression -- Hybrid fire suppression system FOAMS . 13 -- Thermal insulation solutions -- Avoiding HFC-134a emissions in PUF manufacture -- Production of “green” polyols -- Blowing agents for polymeric foams -- Avoidance of GHG emissions in rigid PUF manufacture -- Methods of using a foam blowing agent FUMIGANTS . 15 -- Solar power to kill weeds -- Evaluation of anaerobic soil disinfestation ...